Genetic Diversity and Population Structure of Cannabis Based on the Genome-Wide Development of Simple Sequence Repeat Markers - Zhang, Jiangjiang; Yan, Jiangtao; Huang, Siqi; Pan, Gen; Chang, Li; Li, Jianjun; Zhang, Chao; Tang, Huijuan; Chen, Anguo; Peng, Dingxiang; Biswas, Ashok; Zhang, Cuiping; et al. (Frontiers in Genetics, 2020)
Cannabis has been used as a source of nutrition, medicine, and fiber. However, lack of genomic simple sequence repeat (SSR) markers had limited the genetic research on Cannabis species. In the present study, 92,409 motifs were identified and 63,707 complementary SSR primer pairs were developed. The most abundant SSR motifs had six repeat units (36.60%). The most abundant type of motif was dinucleotides (70.90%), followed by trinucleotides, tetranucleotides, and pentanucleotides. We randomly selected 80 pairs of genomic SSR markers, of which 69 (86.25%) were amplified successfully; 59 (73.75%) of these were polymorphic. Genetic diversity and population structure were estimated using the validated 59 (72 loci) polymorphic SSRs and three phenotypic markers. Three hundred and ten alleles were identified, and the major allele frequency range from 0.26 to 0.85 (average, 0.56), Nei’s genetic diversity ranged from 0.28 to 0.82 (average, 0.56) and the expected heterozygosity ranged from 0.28 to 0.81 (average, 0.56). The polymorphism information content ranged from 0.25 to 0.79 (average, 0.50), the observed number of alleles ranged from 2 to 8 (average, 4.13), and the effective number of alleles ranged from 0.28 to 0.81 (average, 0.5). The Cannabis population did not show mutation-drift equilibrium following analysis via the infinite allele model. A cluster analysis was performed using the unweighted pair group method using arithmetic means based on genetic distances. Population structure analysis was used to divide the germplasms into two subgroups. These results provide guidance for the molecular breeding and further investigation of Cannabis.